Сoronavirus Zigzags of Electronic Distance Learning - A. V. Solovov; A. A. Menshikova (Высшее образование в России, 2021)
The coronavirus pandemic in 2020, which has led to a massive and urgent transition to remote forms of learning, has drawn the attention of almost all of humanity to the issue of e-distance learning (EDL). The purpose of this article is to analyze the didactic aspects of the experience of using EDL methods and technological tools during a pandemic, to assess the potential positive and real negativity of this process, to develop recommendations on the rational use of modern virtual learning environments. The study is based on methods of systemic analysis, pedagogical psychology and didacticism, long-term experience of authors in the field of EDL.The analysis of two main didactic approaches in the modern EDL was carried out: classes in a virtual classroom, most of which copy traditional methods of classroom learning, and predominantly independent cognitive activities of students in learning management systems using specially trained digital educational resources. It has been shown that much of the negative aspects of EDL during the coronavirus pandemic are due to attempts to implement rudiments of the usual classroom learning system with the help of innovative electronic technologies.Recommendations have been made on the structure of the electronic distance course in modern learning management systems, which provide for the freedom to choose the time and place of study with them with the necessary regulation of the content and the learning process inherent in formal education institutions.A number of positive aspects of EDL related to its quality, ever-widening application boundaries, educational potential and economic feasibility have been considered. The importance of properly assessing possible negative aspects of EDL is shown. The reason for which is not in electronic tools, but in didacticly incorrect methods of training with them. To create new teaching methods focused on innovative electronic tools, we need research of psychological and didactic aspects of EDL in the areas of student motivation, digital educational resources development, gamification, teacher training, etc.